Ta’tsīru ṭarīqah al-ghinā’ ‘alā ḥifẓ al-mufradāt fī ta‘līm al-lughah al-‘Arabiyyah li-ṭālibāt al-faṣl al-ḥādī ‘ashara fī al-madrasah al-‘āliyyah al-Islāmiyyah al-ahliyyah “al-Ḥikam” Jatirejo Dīwek Jombang - Devia Ayu Winarsih; Fathur Rohman (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2023)
This research was conducted to determine the effect of the Ghina' method on Mufrodat memorization in learning Arabic in class XI MA Al-hikam Jatirejo students in Jombang district. In this study using quantitative methods. With a population of 44 students from class XI Aliyah and a sample of 24 students. Data collection is done by interview (interview), questionnaire (questionnaire), observation (observation) and a combination of the three. While data analysis is after data from all respondents collected. Classical assumption test (normality test, linearity test, heteroscedasticity test), hypothesis test (t-test), coefficient of determination test (R2). Based on the results of data analysis, it is known that there is a significant influence between the effect of the ghina method on vocabulary memorization. This can be demonstrated by a calculated value of 3.997 and a significance value of 0.001 < 0.05. The contribution of the singing method to vocabulary memorization in learning Arabic reaches 42% of the value of R2 = 0.421 which states that the remaining 58% is caused by other factors that affect vocabulary memorization, such as motivation, subjects, hobbies, and others. From testing the proposed hypothesis, a value of 3,997 can be calculated with a significance value of 0.001 < 0.05. So Ho is rejected and Ha is accepted, meaning that there is a significant influence between the way of singing (X) on the variable memorizing vocabulary (Y).